2021
DOI: 10.48550/arxiv.2106.01267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamical regimes of finite temperature discrete nonlinear Schrödinger chain

Amit Kumar Chatterjee,
Manas Kulkarni,
Anupam Kundu

Abstract: We show that the one dimensional discrete nonlinear Schrödinger chain (DNLS) at finite temperature has three different dynamical regimes (ultra-low, low and high temperature regimes). This has been established via (i) one point macroscopic thermodynamic observables (temperature T , energy density ǫ and the relationship between them), (ii) emergence and disappearance of an additional almost conserved quantity (total phase difference) and (iii) classical out-of-time-ordered correlators (OTOC) and related quantit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Therefore, for large times ∆m(t) = S(−ω 0 )t. (11) In conclusion, in the linear rotator model, the breather mass feels a drift whose coefficient is the component of the power spectrum of the external signal at the breather frequency, S(−ω 0 ) = S(2|z 0 | 2 ). It is therefore useful to determine the power spectrum of the background signal w(t) = −z 1 − z −1 sampled at equilibrium in the absence of breathers.…”
Section: Necessary Ingredients For Frozen Dynamicsmentioning
confidence: 83%
See 1 more Smart Citation
“…Therefore, for large times ∆m(t) = S(−ω 0 )t. (11) In conclusion, in the linear rotator model, the breather mass feels a drift whose coefficient is the component of the power spectrum of the external signal at the breather frequency, S(−ω 0 ) = S(2|z 0 | 2 ). It is therefore useful to determine the power spectrum of the background signal w(t) = −z 1 − z −1 sampled at equilibrium in the absence of breathers.…”
Section: Necessary Ingredients For Frozen Dynamicsmentioning
confidence: 83%
“…The first study of the equilibrium properties of the DNLS equation is due to Rasmussen et al [7], who discuss the statistical mechanics for h ≤ h c within the grandcanonical ensemble (more recent studies can be found in Refs. [8,9,10,11]).…”
Section: Introductionmentioning
confidence: 99%
“…Further, specific features like butterfly speed has also been studied through collective field theory [29]. As in [28], the space time heat maps of OTOC are found prominent to differentiate the ultra-low, low and high temperature regimes that prevail in the discrete nonlinear Schrödinger chain [30].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two conservation laws (mass density a and energy density h, see section 2 for a precise definition) determines a non trivial microcanonical phase diagram, characterized by an infinite temperature-line at finite energy, h c (a) = 2a 2 . The first study of the equilibrium properties of the DNLS equation is due to Rasmussen et al [7], who discuss the statistical mechanics for h h c within the grandcanonical ensemble (more recent studies can be found in [8][9][10][11]).…”
Section: Introductionmentioning
confidence: 99%